Role of endogenous opioids in modulating HSC activity in vitro and liver fibrosis in vivo. Issue 3 (7th November 2007) - De Minicis, S; Candelaresi, C; Marzioni, M; Saccomano, S; Roskams, T; Casini, A; Risaliti, A; Salzano, R; Cautero, N; di Francesco, F; Benedetti, A; Svegliati-Baroni, G
Abstract : Background: Endogenous opioids modulate the growth of nervous and non-nervous cells. Hepatic stellate cells (HSCs) are the main cell phenotype involved in liver fibrogenesis, display molecular markers of neuronal cells and respond to neurotransmitters. Aim: To evaluate the role of endogenous opioids on liver fibrogenesis. Methods: Activated rat HSCs (passage 1–3) were used to evaluate cell proliferation and intracellular signalling pathway activation. Liver fibrosis was induced in rats by dimethylnitrosamine (DMN) administration. Results: Opioid receptors showed a different pattern of expression when measured in quiescent and activated (in vitro and in vivo) HSCs. The activation of opioid receptors increased HSC proliferation and collagen accumulation. Opioid receptor stimulation induced a calcium-dependent protein kinase Cα (PKCα)/extracellular regulated kinase (ERK)/phosphatidylinositol 3-kinase (PI3K) pathway activation that mediated the effect of endogenous opioids on HSC proliferation and collagen synthesis. In DMN-treated rats, the opioid antagonist naloxone reduced α-smooth muscle actin expression (as a marker of HSC activation) and collagen deposition, both measured by morphometry after 5 weeks of treatment. In both DMN-treated rats and human liver biopsies from chronic liver diseases, opioid receptors were observed in HSCs in area of active fibrogenesis. The endogenous opioid met-enkephalin increased its expression in zone 3 hepatocytes close to the area of necrosis after DMN administration and in the cellular target of chronic liver injury in human biopsies, and stimulated HSC proliferation and collagen synthesis. Conclusions: Endogenous opioids released during chronic liver injury participate in the process of liver fibrogenesis by stimulating HSC proliferation and collagen production in a paracrine manner.